Ecotoxicological assessment of biomass-derived furan platform chemicals using aquatic and terrestrial bioassays - Parmaki, Stella; Vasquez Christodoulou, Marlen; Patsalou, Maria; Gomes, Rafael; Simeonov, Svilen P.; Afonso, Carlos A.M.; Koutinas, Michalis (My University, 2024)
An environmental toxicological assessment of fourteen furanic compounds serving as valuable building blocks produced from biomass was performed. The molecules selected included well studied compounds serving as control examples to compare the toxicity exerted against a variety of highly novel furans which have been additionally targeted as potential or current alternatives to biofuels, building blocks and polymer monomers. The impact of the furan platform chemicals targeted on widely applied ecotoxicity model organisms was determined employing the marine bioluminescent bacterium Aliivibrio fischeri and the freshwater green microalgae Raphidocelis subcapitata, while their ecotoxicity effects on plants were assessed using dicotyledonous plants Sinapis alba and Lepidium sativum. Regarding the specific endpoints evaluated, the furans tested were slightly toxic or practically nontoxic for A. fischeri following 5 and 15 min of exposure. Moreover, most of the building blocks did not affect the growth of L. sativum and S. alba at 150 mg L−1 for 72 h of exposure. Specifically, 9 and 11 out of the 14 furan platform chemicals tested were non-effective or stimulant for L. sativum and S. alba respectively. Given that furans comprise common inhibitors in biorefinery fermentations, the growth inhibition of the specific building blocks was studied using the industrial workhorse yeast Saccharomyces cerevisiae, demonstrating insignificant inhibition on eukaryotic cell growth following 6, 12 and 16 h of exposure at a concentration of 500 mg L−1. The study provides baseline information to unravel the ecotoxic effects and to confirm the green aspects of a range of versatile biobased platform molecules.
Keywords: Water Pollutants, Chemical; Aliivibrio fischeri; Biological Assay; Biomass; Ecotoxicology; Furans; Lepidium sativum; Microalgae; Sinapis; Toxicity Tests